Features of Marketing Activities of Companies in the Condition of the Coronavirus Pandemic - BABKO, Natalia; KVIATKO, Tetiana; DUZKRIATCHENKO, Viktoriia; MYKYTAS, Akradii (University Scientific Notes, 2020)
The article identifies the features of marketing in a coronavirus pandemic. The negative consequences of the coronary crisis for enterprises of different spheres of activity have been studied. The main indicators of the efficiency of companies, which showed their growth in the COVID-19 pandemic, as well as changes in marketing activities, which they had to make in order to adapt to the conditions of quarantine, were analyzed. Examples of practical marketing activities of the world’s leading companies are given. The main results of activities in terms of sales of goods and services are presented. The tendencies of development of the leading companies for the period of pandemic are defined, the basic factors of influence on demand and adjustment of the offer in the corresponding markets are formed. Features and practical mechanisms of transition to online business are given, the basic components of tools of transition to online marketing are grouped. The influence of crisis phenomena on market activity of consumers is proved. Marketing tools and methods of influencing consumer behavior, which has undergone significant changes in quarantine are identified. Theoretical features of formation of marketing activity in the conditions of pandemic and directions of marketing transformations in business are worked out. Comparison of the existing theoretical principles and practices of leading companies, resulting in the need to move away from the classical theory of marketing to the introduction of a strategic approach, taking into account the conditions of uncertainty is conducted. The necessity of finding new systems and means of communication and sales promotion through changing the model of consumer behavior and customer demand, in general, is proved. It is determined that under the conditions of the pandemic, e-commerce received a significant development and increase in demand, which also affected the marketing model in terms of business processes between individual market participants. The directions of development of the marketing component in the field of media are outlined, the means of information transfer more popular in the conditions of a pandemic are presented. Examples of leading companies on the reorganization of their marketing activities with emphasis on certain streaming tools, which during this period were in greater demand among consumers are given. The structure of consumption in the field of media is analyzed and the results in the field of marketing policy of communications and advertising are formalized. Recommendations for marketing activities of companies in the conditions of forced transformation of their activities with a focus on total digital are developed.